Análise de viabilidade e proliferação de célulastronco mesenquimais humanas na presença de biomaterial bovino associado ou não a coágulo de fibrina - Heymovski, Janaína Lima (2020)
Much research has been carried out to enable the use of mesenchymal stem cells associated with an application vehicle or support framework in regenerative and tissue engineering therapies. The aim of the present study was to analyze the viability / cytotoxicity and proliferation of human mesenchymal stem cells originating from the pulp of the primary tooth (SHEDs) in the presence of bovine biomaterial associated or not with platelet-rich fibrin (PRF). The studied groups were divided and analyzed as follows: Control Group (C) containing only SHEDs, Group (B) SHEDs + Biomaterial and Group (BP) SHEDs + Biomaterial + PRF. The analyzes were performed at 24, 48 and 72 hours after sowing in 24-well plates. The groups were individually subjected to viability, cytotoxicity and cell proliferation tests using neutral red, MTT and violet crystal respectively, and within 72 hours, scanning electron microscopy (SEM) was performed to record cell morphology. The data were submitted to statistical analysis by ANOVA two factors with a significance level of 5%. The results demonstrated a better performance in the viability / cytotoxicity and proliferation of stem cells for the group (BP) in relation to the group (B) and the group (C). The statistical tests applied showed that the biomaterial factor, time and the interaction between them gave rise to statistically significant results. It can be concluded that human mesenchymal stem cells, originating from the pulp of the primary tooth, proved to be viable, less toxic and more proliferative when associated with PRF and bovine biomaterial and that PRF helped activate the metabolism of stem cells in culture, demonstrating to be an effective resource when a greater cellular response is desired, especially when using bovine biomaterial.